Pulmonary Insufficiency: Advantage of Pulmonary Regurgitation Volume Versus Pulmonary Regurgitation Fraction in a Congenital Heart Disease Mixed Population. Issue 6 (November 2019) - Secchi, Francesco; Chessa, Massimo; Petrini, Marcello; Monti, Caterina B.; Alì, Marco; Cannaò, Paola M.; Di Leo, Giovanni; Sardanelli, Francesco
Abstract : Objective: The objective of this study was to compare the use of pulmonary regurgitation volume (PRV) or indexed PRV (PRVi) with that of pulmonary regurgitation fraction (PRF) in the assessment of patients with pulmonary regurgitation (PR) undergoing cardiac magnetic resonance (CMR) imaging. Materials and Methods: CMR of 176 patients with PR were retrospectively evaluated. Their right ventricular diastolic (end-diastolic volume index [EDVi]) and systolic (end-systolic volume index) volume indexes, stroke volume, and ejection fraction were obtained from cine CMR sequences, whereas phase-contrast flow sequences were analyzed to obtain PRV, PRVi, and PRF. Patients were divided into subgroups, according to underlying pathology and according to PR severity. Correlations between PRV or PRF and RV parameters were studied through Spearman ρ, both in the main group and subgroups. Follow-up examinations were analyzed, and correlations between PRV or PRF from the first CMR examination and volume data from the second were calculated. Results: Tetralogy of Fallot was the main setting of PR (98/179). Overall, EDVi strongly correlates with PRV (ρ=0.592, P <0.001) than with PRF (ρ=0.522, P <0.001), and end-systolic volume index strongly correlates with PRV (ρ=0.454, P <0.001) and PRF (ρ=0.406, P <0.001). As regards subgroup analysis, in moderate or severe PR patients, EDVi strongly correlates ( P =0.043) with PRV (ρ=0.499, P <0.001) than with PRF (ρ=0.317, P <0.001). Follow-up EDVi correlates with PRV (ρ=0.450, P =0.031), but not with PRF. Conclusions: Especially when assessing moderate to severe PR, PRV and PRVi may be better indicators of right ventricular dysfunction than PRF. Moreover, PRV may be a predictor of worsening RV dilation.